Satış Özendirmede Etkili Bir Araç Olarak Insert ve Hiper/Süpermarket Müşterileri Üzerinde Bir Uygulama - (:unkn) unknown (My University, 2003)
Son yıllarda firmaların satış özendirme faaliyetlerini tüketicilere duyurmada alternatif bir medya olarak görülen insert'ten yoğun bir şekilde yararlanılmaktadır. Bu medyanın tüketicilere ulaşımı diğer reklam araçlarına göre daha kolay ve ucuz olduğu için hem üretici, hem de aracı firmalar tarafından tercih edilmektedir. Bu makalede satış özendirme, fiyat indirimi ve insert kavramlarına yer verildikten sonra, bir araştırma ile hiper /süpermarket müşterilerinin insert'e ilişkin yargıları belirlenmeye çalışılmıştır.

In recent years the free standing insert has been intensely used since it seems to be an alternative media in communicating firms' sales promotion to customers. It is preferred by the manufacturers and by the intermediate firms because communication of this media to consumers is relatively easier and cheaper compared to other advertising tools. In this study, the concepts of "sales promotion, price discount and free standing insert" are described and a research is conducted to determine the decision of hyper/supermarket customers about the free standing insert.
Free Standing Insert as an Effective Media in Sales Promotion and a Study on the Hyper/Supermarket Customers